Pengaruh Penggunaan Model pembelajaran Role Playing Berbantuan Media Rotar Terhadap Prestasi Belajar Siswa Sekolah Dasar - Rahmawati, Nur Indah; Bakhruddin, Ahmad; Fakhriyah, Fina (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The low learning achievement of class III students at SDN 1 Bulungcangkring is due to teacher-centered instruction and the use of conventional learning models lacking innovation. This study aims to examine the impact of the Role-Playing learning model, assisted by Rotar media, on student achievement. The Role-Playing method fosters engaging and enjoyable learning, encouraging student participation, while Rotar media enhances enthusiasm and motivation.Method – This study employed a one-group pretest-posttest pre-experimental design, with 33 grade III students as the sample. A paired t-test was used to analyze the differences between pretest and posttest scores, determining the effect of the treatment on learning achievement. Data were collected through observation and interviews.Findings – The study revealed that implementing the Role-Playing learning model assisted by Rotar media significantly improved student learning achievement across all aspects: cognitive (from 42.33 to 73.18), affective (from 42.88 to 76.82), and psychomotor (from 51.48 to 75.82). These results can serve as a reference for teachers in selecting effective methods to enhance student achievement and promote educational policies that prioritize student-centered learning innovations. Research Implications – This study provides a reference for teachers to implement effective, student-centered learning methods and may guide the development of educational policies. However, the limited sample size calls for further research across more diverse schools.